Highly efficient siRNA transfection in macrophages using apoptotic body-mimic Ca-PS lipopolyplex - Lai Y (Dove Medical Press, 2018)
Yueyang Lai,1,* Xuebo Xu,1,* Zhenyu Zhu,1 Zichun Hua1,21The State Key Laboratory of Pharmaceutical Biotechnology, School of Life Sciences, Nanjing University, Nanjing, 210023, China; 2Changzhou High-Tech Research Institute of Nanjing University and Jiangsu Target Pharma Laboratories Inc., Changzhou, China *These authors contributed equally to this work Background: The discovery and development of RNA interference has made a tremendous contribution to the biochemical and biomedical field. However, liposomal transfection protocols to deliver siRNAs to certain types of cells, eg, immune cells, are not viable due to exceedingly low transfection efficiency. While viral delivery and electroporation are two widely adopted approaches to transfect immune cells, they are associated with certain drawbacks such as complexity of preparation, biosafety issues, and high cytotoxicity. We believe amendments can be made to liposomal formulas and protocols to achieve a highly efficient knockdown of genes by liposome-loaded siRNAs.Aim: The aim of this study was to use the apoptotic-mimic Ca-PS lipopolyplex to achieve highly efficient siRNA knockdown of genes in the hard-to-transfect macrophages with reduced cytotoxicity and more efficient cellular uptake.Results: We devised an anionic liposomal formula containing phosphatidylserine to mimic the apoptotic body, the Ca-PS lipopolyplex. Ca-PS lipopolyplex was proven to be capable of delivering and effecting efficient gene knockdown in multiple cell lines at lowered cytotoxicity. Among the two types of macrophages, namely Ana-1 and bone-marrow derived macrophages, Ca-PS lipopolyplex showed an improvement in knockdown efficiency, as high as 157%, over Lipo2000. Further investigations revealed that Ca-PS promotes increased cellular uptake, lysosomal escape and localization of siRNAs to the perinuclear regions in macrophages. Lastly, transfection by Ca-PS lipopolyplex did not induce spontaneous polarization of macrophages.Conclusion: The apoptotic body-mimic Ca-PS lipopolyplex is a stable, non-cytotoxic liposomal delivery system for siRNAs featuring vastly improved potency for macrophages and lowered cytotoxicity. It is speculated that Ca-PS lipopolyplex can be applied to other immune cells such as T cells and DC cells, but further research efforts are required to explore its promising potentials. Keywords: siRNA transfection, anionic liposomes, apoptotic body-mimic, macrophages, Ca-PS lipopolyplex